Upaya Meningkatkan Komitmen Organisasional Dengan Motivasi Dan Kepuasan Kerja Pada Perusahan Alat Berat Dan Bahan Bangunan - Putra, Reza Pratama (Universitas Pendidikan Indonesia, 2018)
The purpose of this paper is to determine the effect of motivation and job satisfaction on the organizational commitment of work employees. This research was conducted in a period of less than 1 year, then the study design was a cross-sectional design. And the method used is an explanatory survey, and a population of 65 employees. The analysis technique used is a multiple linear regression tool processed using SPSS 24.0. The questionnaire was used as a research instrument to collect data from respondents. The findings in this study are that organizational organizational commitment is influenced by motivation and job satisfaction significantly and positively.